Les alternatives aux équipements gérontologiques traditionnels, des laboratoires d'expérimentations à l'épreuve des territoires - Rosenfelder, Cecile (2015)
New habitat’s for elderly are emerging in Europe in the context of ageing population. These habitats can have a multitude of forms, but all of them are build in order to respond to the shortcomings of the gerontological facilities. These are structured from the needs of the elderly and against the nursing homes, which are highly criticized. The proponents of these innovated and original experimentations are developing new care methods for the elderly with frailty in the territories. These new habitats are experimental laboratories and they are established to compete with the traditional gerontological structures